2014
DOI: 10.1093/molbev/msu307
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution ofMomordicaCyclic Peptides

Abstract: Cyclic proteins have evolved for millions of years across all kingdoms of life to confer structural stability over their acyclic counterparts while maintaining intrinsic functional properties. Here, we show that cyclic miniproteins (or peptides) from Momordica (Cucurbitaceae) seeds evolved in species that diverged from an African ancestor around 19 Ma. The ability to achieve head-to-tail cyclization of Momordica cyclic peptides appears to have been acquired through a series of mutations in their acyclic precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 68 publications
2
56
0
Order By: Relevance
“…Oldenlandia affinis) and have similar structural features and biological activities; in particular, they have hydrophobic residues exposed at the surface, and possess anti-HIV and toxic properties (Gustafson et al, 2004;Ireland et al, 2008). Despite possessing identical topology to Mö bius and bracelet cyclotides, members of the trypsin inhibitor subfamily lack hydrophobic residues (Felizmenio-Quimio et al, 2001), have exquisite trypsin inhibitory activity and low cytotoxicity (Hernandez et al, 2000), and have been found exclusively in cucurbitaceous plant species (Mahatmanto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oldenlandia affinis) and have similar structural features and biological activities; in particular, they have hydrophobic residues exposed at the surface, and possess anti-HIV and toxic properties (Gustafson et al, 2004;Ireland et al, 2008). Despite possessing identical topology to Mö bius and bracelet cyclotides, members of the trypsin inhibitor subfamily lack hydrophobic residues (Felizmenio-Quimio et al, 2001), have exquisite trypsin inhibitory activity and low cytotoxicity (Hernandez et al, 2000), and have been found exclusively in cucurbitaceous plant species (Mahatmanto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A third cyclotide subfamily (the trypsin inhibitor subfamily) was based on the discovery of two trypsin inhibitor peptides, MCoTI‐I and MCoTI‐II, extracted from the seeds of Momordica cochinchinensis . Recently this subfamily has been expanded with the discovery of a series of related peptides in other Momordica species . MCoTI‐II and related trypsin inhibitor cyclotides have been pivotal in understanding the biosynthetic processing of cyclic peptides in angiosperms …”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Recently this subfamily has been expanded with the discovery of a series of related peptides in other Momordica species. [8,9] MCoTI-II and related trypsin inhibitor cyclotides have been pivotal in understanding the biosynthetic processing of cyclic peptides in angiosperms. [9] The prototypic cyclotide, kalata B1, first came to notice following a report by a Norwegian doctor who studied the bioactive components in a Congolese traditional medicine called "kalata kalata", which was derived after boiling leaves of Oldenlandia affinis (Roem.…”
mentioning
confidence: 99%
“…Asparaginyl endopeptidase, a protease that recognizes Asp or Asn at the C-terminus of the core peptide for cleavage, has also been recruited by evolution multiple times to perform cyclization of different cyclic peptide families via a transpeptidation reaction. These include (i) kalata-type cyclic peptides (cyclotides), a family of plant macrocyclic peptides containing three disulfide bonds (45-47); (ii) the cyclic knottins -a family of mostly trypsin-inhibitory peptides from the squash family (46,48) and (iii) the single-disulfide PawS-derived peptides of the daisy family (49) and presumably the closely-related PawL-derived peptides, a group of orbitides in the daisy family with an absolutely conserved Asp at the C-terminus of the core peptide (7,8).…”
Section: Biosynthesis Of M Xanthoxyloides Orbitidesmentioning
confidence: 99%